Description of sexuales of Periphyllus singeri (Börner) (Hemiptera, Aphidoidea: Chaitophorinae) - Wieczorek, Karina; Junkiert, Łukasz (Zootaxa, 2011)
The oviparous female and male of the rare aphid, Periphyllus singeri (Börner), are described and illustrated for the first time. Notes on distribution and host plants are presented. Keys are provided to known oviparae and males of European species of Periphyllus.